Altered Connectivity and Synapse Maturation of the Hippocampal Mossy Fiber Pathway in a Mouse Model of the Fragile X Syndrome. (11th January 2017) - Scharkowski, F; Frotscher, Michael; Lutz, David; Korte, Martin; Michaelsen-Preusse, Kristin
Abstract: The Fragile X syndrome (FXS) as the most common monogenetic cause of cognitive impairment and autism indicates how tightly the dysregulation of synapse development is linked to cognitive deficits. Symptoms of FXS include excessive adherence to patterns that point to compromised hippocampal network formation. Surprisingly, one of the most complex hippocampal synapses connecting the dentate gyrus (DG) to CA3 pyramidal neurons has not been analyzed in FXS yet. Intriguingly, we found altered synaptic function between DG and CA3 in a mouse model of FXS ( fmr1 knockout [KO]) demonstrated by increased mossy fiber-dependent miniature excitatory postsynaptic current (mEPSC) frequency at CA3 pyramidal neurons together with increased connectivity between granule cells and CA3 neurons. This phenotype is accompanied by increased activity of fmr1 KO animals in the marble burying task, detecting repetitive and obsessive compulsive behavior. Spine apparatus development and insertion of AMPA receptors is enhanced at postsynaptic thorny excrescences (TEs) in fmr1 KO mice. We report age-dependent alterations in TE morphology and in the underlying actin dynamics possibly linked to a dysregulation in profilin1 expression. TEs form detonator synapses guiding CA3 network activity. Thus, alterations described here are likely to contribute substantially to the impairment in hippocampal function and therefore to the pathogenesis of FXS.